Modelling surface temperatures on 3G artificial turf - Gustin, M.; Fleming, P. R.; Allinson, D.; Watson, S. (Proceedings, 2018)
High surface temperatures are often recorded on or close to the surface of an artificial turf pitch (ATP). Many literature sources from different countries have reported surface temperatures on artificial pitches rising up to 90-95 °C on hot days, which has raised numerous concerns about health risks for adult and child users. This study has investigated the thermal behavior of an instrumented 3rd generation ATP at Loughborough University in the UK, and related data also collected from several similar ATPs and a natural turf field. The data show the ATP is warming up and cooling down very quickly, up to 2.5-3.0 °C per minute. Solar radiation is the main factor driving the surface temperature fluctuations. A numerical model was developed to predict the surface temperatures and showed good approximation to the observed data. The model was used to show peak surface temperatures could be significantly reduced by increasing the albedo of the surface.